The potential of hyaluronic acid in the treatment of periodontal inflammation - Bousquet, Cécile (2017)
Hyaluronic acid is a naturally occurring linear polysaccharide identified in all periodontal tissues in varying quantities. It is a very promising alternative as a mediator of periodontal tissue regeneration, because of its vast presence in periodontal tissues and its anti-inflammatory capacity. The objective of this literature review was to evaluate the potential of hyaluronic acid in the treatment of periodontal inflammation. A survey was conducted between November 2016 and March 2017 in MEDLINE, B-on, Scopus and Google Scholar database. Manuscript analysis was substantiated on Meta-Analysis Reporting Standards. The languages elected for articles selection were English, French, Portuguese and Spanish, and the time limit was the period from 2007 to 2017. That search resulted in 33 articles with the eligibility criteria. Hyaluronic acid has shown anti-inflammatory, anti-oedematous and anti-bacterial effects in the treatment of periodontal diseases. In the treatment of gingivitis or periodontitis, hyaluronic acid presents advantages when used alone or used as an adjuvant. Despite hyaluronic acid identified properties, further long-term studies need to be carried out discussing application time, quantity of application, different forms and concentrations. These studies could also optimize administration protocols and establish proper recommendations for its use. Hyaluronic acid presents beneficial effects on periodontal inflammation, with importance on a microbiological level with favorable clinical outcomes.